Implementation of Gayo Lues Regent Regulation No. 4 of 2021 by the Tourism Office in the Management of Agusen Tourism from the Perspective of Fiqh Siyasah Tanfidziyah - Joni Syafrijal; Fajrul Wadi (Tanfizi : Journal of Islamic Constitutional and Political Law, 2025)
Gayo Lues Regent Regulation No. 4 of 2021 is a strategic step in managing tourism potential in Agusen Village, Gayo Lues Regency, which is known for its natural beauty, culture, and local traditions. This study aims to analyze the implementation of the policy through the Fiqh Siyasah Tanfidziyah approach, which prioritizes benefit and sustainability. qualitative research method with data collection through observation, interviews, and document analysis. The implementation of Gayo Lues Regent Regulation No. 4 of 2021 in Agusen Village has had a significant positive impact on local tourism management. Then the implementation of tourism policy in Agusen Village is in line with the principles of Fiqh Siyasah Tanfidziyah, which emphasizes sustainability and community benefit. Therefore, it is important for the government to continue to evaluate and adapt existing policies, so that they can be more responsive to the needs of local communities. In addition, there needs to be increased education and socialization about the importance of sustainable tourism to the community. It is also recommended that local governments strengthen collaboration with various parties, including NGOs and the private sector, to attract more investment and technical support in tourism development. With these steps, it is hoped that tourism management in Agusen Village can be optimized, contribute to the local economy, and preserve the local culture